EFFECTIVENESS OF STUDENT WORKSHEET BASED ON GUIDED INQUIRY LEARNING TO FACILITATE STUDENT’S HIGHER ORDER THINKING SKILLS - Sulis Idillah Ulfa; Mohammad Budiyanto; Enny Susiyawati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This study aimed to describe the Effectiveness of Student Worksheet Based on Guided Inquiry Learning to Facilitate Student’s Higher Order Thinking Skills. The data collection method was obtained from the test method with the type of one group pretest-posttest design research. The subject was conducted in class VIII C SMP Negeri 3 Burneh with 25 students. The effectiveness to Facilitate Student’s Higher Order Thinking Skills showed by N-gain score and student’s activities. The result of the average score of students in the pre-test 26.16 while the post-test 74.66 with n-Gain 0.65 in the medium category then the results of observations of student's activities showed that the relevant activities were more dominant in each successive meeting by 94,51%, 95,29%, 98,25%,. The conclusion of this research is the Student Worksheet Based on the Guided Inquiry Learning to Facilitate Student’s Higher Order Thinking Skills declared feasible in terms of effectiveness. Keyword : Student Worksheet, Guided Inquiry, HOTS.